Closed ventilation and filtering system for cleaning of welding aerosols at deposition - Chigarev, V; Logvinov, Yu (Problems of Tribology, 2021)
In the article the questions of development of construction of the closed ventilation and filtering system (CVFS) are considered on cleaning of air-gas mixture at deposition. The offered system consists of gas in-take, filters, containers for assembling of hard parts, hard constituent of welding aerosol (TSSA), by the gaseous constituent of welding aerosol (GSSA) and corps, special vent system with adjusting of speed and volume of extraction. Conducted research for cleaning of welding aerosols (SA) at deposition of high wear proof alloys of type of sormite with the use of the CVFS. Special CVFS is used, filters in particular mechanical, electric, chemical (sorption). Extraction of air-gas mixture from the area of melting of electrode and welding bath of is carried out by the pipe of small diameter, with adjusting of speed and volume of extraction passes the system of filtration the special vent system where clears up from TSSA. Thus cleared gas mixture is used as gas defense at depositing. It is necessary it is not simple to catch SA, but to filter in the closed system, clean and give filtered clean y air in the area of deposition, technology and metallurgical properties of process of depositing must not be broken here. Features of the mechanical cleaning are in technologies of deposition, characterized that air-gas mixture has a temperature which influences on a sorbent. The mechanical cleaning by the centrifugal chamber of cleaning (CCC) is the modernized cyclone filter where centrifugal forces and gravities were used. Differs from existent cyclic filters a presence by a conical spiral insertion and rearranged surface of cone which engulfs it. In the entrance tangential union coupling appears, divided aero mixture into a few streams of entered in a spiral insertion. In the electric filter (electrostatic) electric forces operate on particles and gas molecules (based on the phenomena ionization of gas molecules, by an electric charge in the electric field). An electric charge is revealed to the particles, and they under the action of the electric field are besieged from a gas stream. If such gas, containing the several of transmitters of charges, to place between electrodes, connected with the source of high voltage, ions and electrons will begin to move to on power the field lines . This is important during neutralization of GSSA